2016
DOI: 10.5901/mjss.2016.v7n1s1p181
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Styles and Gender as Predictors of Social Intelligence among Adolescents in Idoma Land

Abstract: The research investigated parenting style and gender as predictors of social intelligence among adolescents in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…It could be due to the fact that in Pakistan, many women experience gendered disadvantages including limited education and less employment outside of the home (Qadir et al, 2011). However, Terwase et al (2016) also found similar results that gender did not significantly predict SI among adolescents in Idoma Land. Contrary to their findings, Saxena and Jain (2013) showed that female students possess more SI than male students and arts students had greater SI than students of other streams.…”
Section: Discussionmentioning
confidence: 75%
“…It could be due to the fact that in Pakistan, many women experience gendered disadvantages including limited education and less employment outside of the home (Qadir et al, 2011). However, Terwase et al (2016) also found similar results that gender did not significantly predict SI among adolescents in Idoma Land. Contrary to their findings, Saxena and Jain (2013) showed that female students possess more SI than male students and arts students had greater SI than students of other streams.…”
Section: Discussionmentioning
confidence: 75%
“…Walker and Foley (1973) define social intelligence as the ability to deal with people, to understand others' feelings and thoughts, and to make precise judgements or inferences about people's emotions, temperaments, and motivations. While Wedeck (1947) considers social intelligence as the ability to evaluate people's moods, emotions, and motivations in an acceptable manner, Terwase, Ibaishwa, and Enemari (2016) define it as the ability to understand the events around a person and react to these events in a personal and social way. In another definition, social intelligence is considered as the ability to be aware of social situational contexts, to deal with difficulties effectively, to understand others' concerns, feelings, and emotional states, to know what, when, and how to speak up while being convincing and open, and to have positive relationships with others (Rahim, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Diğer insanların ruh hâllerine, mizaçlarına, motivasyonlarına ve amaçlarına gösterilen hassasiyet gibi başkaları ile iletişim kurarken kullanılan becerilerdir (Renner ve Feldman, 2015). Sosyal zekâ yalnızca bireyin kendinde ya da karşısındakinde değil, çevresinde olup bitenleri de anlama etkileyebilme ve farklı sosyal ortamlarda iyi ilişkiler kurabilme kapasitesidir (Terwase, Ibaishwa ve Enemari, 2016).…”
Section: Introductionunclassified